Singapore - Vietnam Strategic Partnership: New Initiatives Needed - Le, Hong Hiep (2016)
The Singapore-Vietnam strategic partnership has strong foundations, but the two countries need to look for bolder and more substantive measures to further deepen their ties. In defence cooperation, anti-piracy joint patrols and bilateral training arrangements are among initiatives to be considered.